2013
DOI: 10.1371/journal.pone.0060893
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Porcine Plasmacytoid Dendritic Cells by Cytokines

Abstract: Plasmacytoid dendritic cells (pDC) are the most potent producers of type-I interferon (IFN) and represent the main interferon (IFN)-α source in response to many viruses. Considering the important roles played by type I IFN’s, not only as antiviral effectors but also as potent alarming cytokine of the immune system, we investigated how such responses are regulated by various cytokines. To this end, we stimulated enriched pDC in the presence or absence of particular cytokines with a strong activator, CpG DNA, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The regulatory cytokine IL-10 was thought to strongly impact PRRSV pathogenesis and was one of the proposed mechanisms used by PRRSV to escape the innate and adaptive immune system. However, the induction of IL-10 by PRRSV is not clearly established [11,51], although its presence suppresses type I IFN induction in pDC [52,53]. It has been reported that PRRSV could induce IL-4 in the serum [20] and IFN-γ both in the serum [54] and in the lungs [48] of infected pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The regulatory cytokine IL-10 was thought to strongly impact PRRSV pathogenesis and was one of the proposed mechanisms used by PRRSV to escape the innate and adaptive immune system. However, the induction of IL-10 by PRRSV is not clearly established [11,51], although its presence suppresses type I IFN induction in pDC [52,53]. It has been reported that PRRSV could induce IL-4 in the serum [20] and IFN-γ both in the serum [54] and in the lungs [48] of infected pigs.…”
Section: Discussionmentioning
confidence: 99%
“…DCs are the most potent antigen-presenting cells (APCs), whose function is to initiate an adaptive immune response. Activation and maturation of DCs are induced by infectious agents and inflammatory products [7] , [30] , as well as by host cytokines [31] , [32] . Cytokines affect DC differentiation and are important in controlling states of perpetual inflammation, as can be seen in CP, when DCs are continuously exposed to antigens [33] .…”
Section: Discussionmentioning
confidence: 99%
“…For opsonization assays, we made use of a previously established assay based on the ability of plasmacytoid dendritic cells (pDCs) to secrete enhanced INF-α in response to immune complexed virus compared with free virus via an Fcγ receptors (FcγR)-dependent pathway ( 19 21 ). To this end, peripheral blood mononuclear cells (PBMCs) were freshly isolated from blood of our SPF pigs using ficoll-paque density centrifugation (1.077 g/l, Amersham Pharmacia Biotech).…”
Section: Methodsmentioning
confidence: 99%